Investigation into the Role of Potentially Contaminated Feed as a Source of the First‐Detected Outbreaks of Porcine Epidemic Diarrhea in Canada. Issue 5 (7th August 2014) - Pasick, J.; Berhane, Y.; Ojkic, D.; Maxie, G.; Embury‐Hyatt, C.; Swekla, K.; Handel, K.; Fairles, J.; Alexandersen, S.
Summary In January 2014, approximately 9 months following the initial detection of porcine epidemic diarrhea (PED) in the USA, the first case of PED was confirmed in a swine herd in south‐western Ontario. A follow‐up epidemiological investigation carried out on the initial and 10 subsequent Ontario PED cases pointed to feed as a common risk factor. As a result, several lots of feed and spray‐dried porcine plasma (SDPP) used as a feed supplement were tested for the presence of PEDV genome by real‐time RT‐PCR assay. Several of these tested positive, supporting the notion that contaminated feed may have been responsible for the introduction of PEDV into Canada. These findings led us to conduct a bioassay experiment in which three PEDV‐positive SDPP samples (from a single lot) and two PEDV‐positive feed samples supplemented with this SDPP were used to orally inoculate 3‐week‐old piglets. Although the feed‐inoculated piglets did not show any significant excretion of PEDV, the SDPP‐inoculated piglets shed PEDV at a relatively high level for ≥9 days. Despite the fact that the tested PEDV genome positive feed did not result in obvious piglet infection in our bioassay experiment, contaminated feed cannot be ruled out as a likely source of this introduction in the field where many other variables may play a contributing role.